Ethylene / alpha-olefin copolymer, preparation method and application of ethylene / alpha-olefin copolymer in photovoltaic packaging film

By preparing ethylene/α-olefin copolymers with specific properties, the decomposition problem of ethylene/vinyl acetate copolymers and the gap in processing performance between new companies have been solved, achieving efficient production and performance improvement of photovoltaic encapsulation films, which are suitable for the photovoltaic encapsulation film field.

CN121673455APending Publication Date: 2026-03-17WANHUA CHEM GRP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511986419.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-26
Publication Date
2026-03-17

AI Technical Summary

Technical Problem

Existing ethylene/vinyl acetate copolymers decompose and produce harmful gases during long-term use, affecting the lifespan and efficiency of solar cell devices. Furthermore, the ethylene/α-olefin copolymers from newly established companies have shortcomings in processing performance and basic properties, making it difficult to meet the requirements of high-efficiency production.

Method used

An ethylene/α-olefin copolymer with a specific melting point, zero-shear viscosity, and shear viscosity ratio range was prepared. The processing temperature and shear rate were optimized by cross-hierarchical chromatography and specific branching factor control. The polymerization reaction was carried out using transition metal catalysts and co-catalysts to ensure the material's flowability and formability at appropriate temperatures.

Benefits of technology

This has enabled the efficient production of photovoltaic encapsulation films, improved light transmittance and peel strength, reduced production energy consumption, and enhanced the stability and competitiveness of the materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses an ethylene / alpha-olefin copolymer, a preparation method and application of the ethylene / alpha-olefin copolymer in a photovoltaic packaging film. The copolymer comprises the following features: a) the melting point Tm is 50-75 DEG C; b) a zero shear viscosity [eta] 0 of 1 * 10 < 4 >-8 * 10 < 4 > Pa.s; c) the viscosity ratio n is 8-22 when the shearing rate is 1 rad / s and the shearing rate is 100 rad / s; and d) through a cross fractionation chromatography CFC test, the mass ratio of the fraction obtained by elution at 40 DEG C is 0.5-1.2 wt%, and the branching degree factor g'is in the range of 0.90-0.97. The copolymer provided by the invention has specific lubricant and shear thinning properties, so that the copolymer has excellent processability in the process of preparing a photovoltaic adhesive film, and also has improved light transmittance and peel strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of photovoltaic encapsulation materials technology, specifically relating to an ethylene / α-olefin copolymer, its preparation method, and its application in photovoltaic encapsulation films. Background Technology

[0002] Today, solar cells are typically assembled using modules. The photovoltaic encapsulation film is the bonding material between the glass, cells, and backsheet in a photovoltaic module. It is located on the top and bottom sides of the cell and its main functions include: bonding the photovoltaic cell to the glass and backsheet; enabling light coupling between the cell and the glass to ensure that the solar radiation transmittance exceeds 90%; and providing support and protection by acting as a physical barrier between the cell and other components.

[0003] Currently, mainstream solar cell sealants on the market typically use ethylene / vinyl acetate copolymers or ethylene / α-olefin copolymers. However, if ethylene / vinyl acetate copolymers are used as a component of solar cell sealants, they will decompose during long-term use, producing components such as acetic acid gas, which will significantly affect the lifespan and efficiency of the solar cell device.

[0004] Conversely, ethylene / α-olefin copolymers possess superior properties such as high light transmittance, high resistance to PID (polyvinyl chloride), high water resistance, and high heat resistance, and are now widely used. The flexible, coiled structure formed by the α-olefin branches in ethylene / α-olefin copolymers constitutes the amorphous regions (rubber phase) with rubber-like elasticity, while the crystalline regions (plastic phase) of the polyethylene segments serve as physical crosslinking points. At room temperature or low temperatures, the crystalline regions remain stable, and the material exhibits rubber-like elasticity; at high temperatures, the crystalline regions melt and break down, and the material transforms into a molten fluid state, facilitating production and processing.

[0005] The preparation of photovoltaic encapsulation films can employ conventional methods in this field, including the following steps: high-temperature premixing of raw materials, melt extrusion, casting into a film, cooling and slitting, and winding. Typically, polymers, crosslinking agents, co-crosslinking agents, coupling agents, and antioxidants are uniformly mixed. The premix is ​​then fed into a single-screw or twin-screw extruder, where the screws are heated in sections. After the polymer is melted and extruded, the melt flows through a filter screen, is cast into a film, and then cooled, slid, and wound. Compared to established competing brands, many new companies' self-produced brands still lag significantly in terms of basic performance and processing. Currently, there is a need to develop high-performance ethylene / α-olefin copolymers that can ensure the stability of the material's basic properties and the high efficiency of production and processing within a suitable temperature range, thereby enhancing market competitiveness. Summary of the Invention

[0006] To address the above technical problems, this invention proposes an ethylene / α-olefin copolymer, its preparation method, and its application in photovoltaic encapsulation films.

[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows:

[0008] An ethylene / α-olefin copolymer, comprising the following characteristics:

[0009] a) Melting point T m The temperature is 50-75℃;

[0010] b) At a temperature of T m +15°C to T m At +30℃, the zero-shear viscosity η0 is 1×10⁻⁶. 4 -8×10 4 Pa·s, preferably 4×10 4 -6×10 4 Pa·s;

[0011] c) At a temperature of T m +15°C to T m At +30℃, the viscosity ratio n at shear rates of 1 rad / s and 100 rad / s is 8-22, preferably 8-15, and more preferably 8-11.

[0012] d) The mass percentage of the fraction obtained by cross-fractional chromatography CFC test at 40°C is 0.5-1.2wt%, preferably 0.8-1.0wt%, and the branching factor g′ is in the range of 0.90-0.97, preferably 0.90-0.93.

[0013] In this invention, the branching factor g′ is an index used to measure the ratio of the intrinsic viscosity of a sample at the same molecular weight to the intrinsic viscosity of a linear reference sample, and its calculation formula is as follows:

[0014] g′=[η] sample (M) / [η] linear (M)

[0015] Among them, [η] sample [η] refers to the intrinsic viscosity of the ethylene / α-olefin copolymer sample. linear It refers to the intrinsic viscosity of a linear reference sample with the same molecular weight (i.e., the linear sample of polyethylene), where M represents the weight-average molecular weight (Mw), ranging from 5000 to 50000.

[0016] As mentioned above, the processing temperature of the prepared ethylene / α-olefin copolymer should not be too high, as excessively high temperatures will cause the premixed additives to decompose, reducing their antioxidant, anti-aging, and crosslinking abilities. Conversely, the temperature should not be too low, as this will result in more melt crystal points, increased filter mesh pressure, reduced processing efficiency, and increased production losses leading to higher costs. Therefore, a suitable processing temperature is defined as T. m +15°C to T m Within the +30℃ range, at the above processing temperatures, it was found that excessively high viscosity ratios (n) at shear rates of 1 rad / s and 100 rad / s resulted in poor polymer molding during processing, uneven film thickness during casting, and the formation of easily ruptured cavities. Conversely, excessively low viscosity ratios (n) significantly increased filter pressure during screw extrusion, severely impacting the efficiency of casting and pressing. Therefore, a reasonable viscosity ratio range was derived. Furthermore, by limiting the mass percentage of eluted fractions and the branching factor (g′) range at ambient temperature, the polymer's processability was further improved. When these small molecular chains are present in the polymer, these short chains, which do not reach the entanglement molecular weight, cannot form effective molecular entanglement and act as a "lubricant," further reducing intermolecular frictional resistance, making the material flow more easily during extrusion and casting, and reducing the energy consumption of processing equipment.

[0017] As described above, the ethylene / α-olefin copolymer of the present invention is characterized by a melting point (Tm) of 50°C to 75°C. If the melting point (Tm) value deviates from the above range and is too low or too high, the zero-shear viscosity may not meet the range defined in the present invention.

[0018] In some preferred embodiments, the ethylene / α-olefin copolymer has a weight-average molecular weight of 30,000-150,000 and a molecular weight distribution of 1.8 to 3.5.

[0019] In some preferred embodiments, the ethylene / α-olefin copolymer has a melt flow index (MFR) of 1-30 g / 10 min at 190 °C and a load of 2.16 kg, particularly 1-20 g / 10 min, and even more particularly 5-15 g / 10 min.

[0020] If the melt index is less than 1 g / 10 min, the production rate may be reduced due to high load, and if the melt index is greater than 30 g / 10 min, film forming will be difficult, and defects may occur that make it unsuitable for use as a sealant film.

[0021] In some preferred embodiments, the α-olefin copolymer is selected from one or more of propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-heptene, 1-octene, 1-decene, 1-undecene, 1-dodecene, 1-tetradecene, 1-hexadecene, and 1-eicosene.

[0022] In some preferred embodiments, the α-olefin content in the ethylene / α-olefin copolymer is 20-50 wt%.

[0023] A method for preparing an ethylene / α-olefin copolymer as described above includes the following steps:

[0024] Ethylene and α-olefins are polymerized in the presence of a transition metal catalyst as shown in Formula I to obtain an ethylene / α-olefin copolymer.

[0025]

[0026] R1 and R2 are each independently selected from hydrogen and fluorine;

[0027] Among them, R3 is selected from hydrogen, C1-C 20 Alkyl, C3-C 20 cycloalkyl, C2-C 20 Straight-chain alkyl-terminated alkenyl, C1-C 20 Alkoxy, C6-C 20 Aryl, C7-C 20 arylalkoxy, C7-C 20 Arylalkyl;

[0028] M is selected from Ti, Zr, or Hf.

[0029] Furthermore, the compound represented by Formula I can be any of the following compounds, and is not limited to the following structural compounds:

[0030]

[0031] As a preferred embodiment, a co-catalyst is also added to the polymerization reaction system, the co-catalyst comprising an organic compound containing a Group IIIA element.

[0032] In a preferred embodiment, the co-catalyst comprises any one of the compounds shown in Formula II and Formula III, and optionally a compound shown in Formula IV:

[0033] -[Al(R a )-O] n -Ⅱ

[0034] Among them, R a Selected from C1-C 10 Alkyl or halogen-substituted C1-C 10 Alkyl group, n≥2;

[0035] A(R b )3Ⅲ

[0036] Among them, R b Selected from C1-C20 Alkyl or halogen-substituted C1-C 20 Alkyl group, where A is aluminum

[0037] [DH] + [ZT4] - IV

[0038] Among them, [D] + It is an organic cation; Z is a Group IIIA element;

[0039] T is selected from R c Substituted or unsubstituted C6-C 20 Aryl, R c Substituted or unsubstituted C6-C 20 Alkyl, the R c Selected from halogens, C1-C 20 Alkyl, C1-C 20 Alkoxy, C6-C 20 Phenoxy group.

[0040] In the above-mentioned cocatalysts, the compound represented by Formula II can be any one of methylaluminoxane, ethylaluminoxane, isobutylaluminoxane, butylaluminoxane, and octylaluminoxane.

[0041] Examples of compounds represented by chemical formula III may include trimethylaluminum, triethylaluminum, triisobutylaluminum, tripropylaluminum, tributylaluminum, triisopropylaluminum, trisec-butylaluminum, tripentylaluminum, triisopentylaluminum, trihexylaluminum, trioctylaluminum, triphenylaluminum, tri-p-tolylaluminum, trimethylboron, triethylboron, tripropylboron, tributylboron, triisobutylboron, etc.

[0042] Examples of compounds represented by Formula IV may include triethylammonium tetra(phenyl)boron, tributylammonium tetra(phenyl)boron, trimethylammonium tetra(phenyl)boron, tripropylammonium tetra(phenyl)boron, trimethylammonium tetra(p-tolyl)boron, trimethylammonium tetra(o-,p-dimethylphenyl)boron, tributylammonium tetra(p-trifluoromethylphenyl)boron, trimethylaluminum tetra(p-trifluoromethylphenyl)boron, tributylammonium tetra(pentafluorophenyl)boron, and N,N-diethylphenylammonium tetra(phenyl)boron. N,N-Dimethylphenylammonium tetra(phenyl)boron, diethylammonium tetra(pentafluorophenyl)boron, triphenylphosphonium tetra(phenyl)boron, trimethylphosphonium tetra(phenyl)boron, triethylammonium tetra(phenyl)aluminum, tributylammonium tetra(phenyl)aluminum, trimethylammonium tetra(phenyl)aluminum, tripropylammonium tetra(phenyl)aluminum, trimethylammonium tetra(p-tolyl)aluminum, tripropylammonium tetra(p-tolyl)aluminum, triethylammonium tetra(o,p-dimethylphenyl)aluminum, tributylammonium tetra(p-trifluoromethylphenyl) Aluminum, trimethylammonium tetra(p-trifluoromethylphenyl)aluminum, tributylammonium tetra(pentafluorophenyl)aluminum, N,N-dimethylphenylammonium tetra(phenyl)aluminum, N,N-diethylphenylammonium tetra(phenyl)aluminum, N,N-diethylphenylammonium tetra(pentafluorophenyl)aluminum, diethylammonium tetra(pentafluorophenyl)aluminum, triphenylphosphonium tetra(phenyl)aluminum, trimethylphosphonium (phenyl)aluminum, tripropylammonium tetra(p-tolyl)boron, triethylammonium tetra(o-,p-dimethylphenyl)boron, trimethylphosphonium tetra( Any one of the following: (phenyl)aluminum, tripropylammonium tetra(p-tolyl)boron, triethylammonium tetra(o-,p-dimethylphenyl)boron, tributylammonium tetra(p-trifluoromethylphenyl)boron, triphenylcarbium tetra(p-trifluoromethylphenyl)boron, triphenylcarbium tetra(pentafluorophenyl)boron, triphenylcarbium tetra(octafluoronaphthyl)boron, triethylammonium tetra(octafluoronaphthyl)boron, N,N-dimethylphenylammonium tetra(octafluoronaphthyl)boron, and N,N-diethylphenylammonium tetra(octafluoronaphthyl)boron.

[0043] As a preferred embodiment, the amount of the compound shown in Formula II and / or Formula III in the polymerization reaction is 50-1000 times the molar amount of the transition metal catalyst.

[0044] The amount of the compound shown in Formula IV in the polymerization reaction is 0-10 times the molar amount of the transition metal catalyst.

[0045] Application of an ethylene / α-olefin copolymer as described above or an ethylene / α-olefin copolymer prepared by the method described above in photovoltaic encapsulation films.

[0046] The present invention has the following beneficial effects:

[0047] The ethylene / α-olefin copolymer that meets all the conditions defined in this invention has specific "lubricant" and shear-thinning properties, which makes it excellent in processing photovoltaic films, enabling efficient production, while also providing improved light transmittance and peel strength. It can be widely used in various applications in the electrical and electronic industries, especially in the field of photovoltaic films.

[0048] In the following description, preferred embodiments will be presented for better understanding of the invention. However, the embodiments described below are merely for the purpose of understanding the invention, and the scope of the invention is not limited thereto. Detailed Implementation

[0049] The present invention will be further illustrated below with specific embodiments. These embodiments are merely illustrative and do not limit the scope of the invention.

[0050] Unless otherwise specified, the raw materials and reagents used in the following embodiments of the present invention are all commercially available materials. Specifically:

[0051] Toluene, sodium hydroxide, ethyl acetate, n-hexane, Isopar E, and 1-octene were all purchased from Inocare.

[0052] 2-Hydroxybenzylamine, purchased from Aladdin Biochemical Company;

[0053] n-Butyllithium (n-BuLi) and titanium(IV) chloride tetrahydrofuran complex were purchased from Yanfeng Technology Co., Ltd.

[0054] 1H-indole-2-carboxaldehyde, 2-acetylindole, and 2-phenylmethyl ketone-1H-indole were all purchased from Shanghai Bide Reagent Co., Ltd.

[0055] 6-Fluoro-1H-indole-2-carboxaldehyde, 5-Fluoro-1H-indole-2-carboxaldehyde, and 5,6-difluoro-1H-indole-2-carboxaldehyde were all purchased from Leyan Reagents.

[0056] Modified methylaluminoxane (MMAO-7), purchased from Norio Corporation;

[0057] The ethylene was purchased from Linde Gases.

[0058] Catalyst A: Purchased from Panjin Yanfeng Technology Co., Ltd.

[0059] Catalyst B: Purchased from Panjin Yanfeng Technology Co., Ltd.

[0060] Catalyst c: Purchased from Jiangsu Xinnoco Catalyst Co., Ltd.

[0061] Catalyst d: Purchased from Jiangsu Xinnoco Catalyst Co., Ltd.

[0062] [Preparation Example 1]

[0063]

[0064] Catalyst I-1 was prepared according to the following method:

[0065] Step 1: In a 500 mL Shrek flask equipped with a magnetic stirrer and a reflux evaporator, add 200 mL of toluene as the reaction solvent. Heat the oil bath to 120 °C, and add 1H-indole-2-carboxaldehyde (5.0 g, 34.4 mmol) and 2-hydroxybenzylamine (3.81 g, 30.9 mmol). Maintain the reaction at this temperature, and slowly add p-toluenesulfonic acid (5.92 g, 34.4 mmol) dropwise for about 4-6 hours. Monitor the reaction progress by TLC. Once the reactants are completely consumed, stop the reaction. After the reaction system temperature drops to room temperature, pour the reaction solution into 100 mL of ice water. Slowly add a water-saturated solution of sodium hydroxide (2.75 g, 68.8 mmol) dropwise to the reaction solution to adjust the pH to 7-8. Extract with 400 mL of ethyl acetate, dry with 30 g of anhydrous magnesium sulfate, and concentrate under reduced pressure to remove the solvent. Concentrate to obtain a pale yellow solid, which is the intermediate.

[0066] H 1 NMR(400MHz, CDCl3)δ2.62(2H,d),5.32-5.35(1H,s),6.77-7.12(7H,dd),7.54(1H,dd),7.67(1H,dd),8.28(1H,s),11.92(1H,s)

[0067] Step 2: The intermediate (500 mg, 2 mmol) was placed in a 250 mL reaction flask, and 150 mL of dry toluene solution was added. After purging with nitrogen three times, the mixture was cooled to -10 °C to 0 °C under nitrogen protection and stirred. n-BuLi (1.6 mol / L, 2.8 mL, 4.4 mmol) was added dropwise. After the addition was complete, the reaction was brought to room temperature and stirred for 30 min. Titanium(IV) tetrahydrofuran complex (0.66 g, 2 mmol) was added, and the reaction was stirred overnight. After the reaction was completed, the mixture was filtered through dry diatomaceous earth. The filtrate was concentrated to obtain an oily compound, which was transferred to a glove box and recrystallized at -20 °C with dry n-hexane. After filtration, catalyst formula I-1 was obtained.

[0068] H 1 NMR(400MHz, CDCl3)2.60(2H,d),6.66(1H,dd),6.83-6.89(3H,dd),7.06-7.09(2H,dd),7.33(1H,t),7.52(1H,s),7.92-7.95(2H,dd)

[0069] [Preparation Example 2]

[0070] Catalyst I-2 was prepared using essentially the same method as in Preparation Example 1, except that 1H-indole-2-carboxaldehyde was replaced with 2-acetylindole.

[0071]

[0072] H 1 NMR (400MHz, CDCl3) δ1.82(3H,s),2.60(2H,d),6.62(1H,dd),6.85-6.91(3H,dd),7.07-7.10(2H,dd),7.33(1H,t),7.94-7.96(2H,dd)

[0073] [Preparation Example 3]

[0074] Catalyst I-3 was prepared using essentially the same method as in Preparation Example 1, except that 1H-indole-2-carboxaldehyde was replaced with 2-phenylmethyl ketone-1H-indole.

[0075]

[0076] H 1 NMR(400MHz, CDCl3)δ4.82(2H,t),6.66(1H,dd),6.83-6.89(3H,dd),7.06-7.09(2H,dd),7.33(1H,tt),7.51-7.53(3H,DD),

[0077] 7.83-7.93 (4H,dd)

[0078] [Preparation Example 4]

[0079] Catalyst I-4 was prepared using essentially the same method as in Preparation Example 1, except that 1H-indole-2-carboxaldehyde was replaced with 6-fluoro-1H-indole-2-carboxaldehyde.

[0080]

[0081] H 1 NMR(400MHz, CDCl3)δ2.60(2H,d),6.66(1H,dd),6.83-6.89(3H,dd),7.06-7.09(2H,dd),7.52(1H,t),7.54(1H,s),8.43(1H,dd)

[0082] [Preparation Example 5]

[0083] Catalyst I-5 was prepared using essentially the same method as in Preparation Example 1, except that 1H-indole-2-carboxaldehyde was replaced with 5-fluoro-1H-indole-2-carboxaldehyde.

[0084]

[0085] H 1 NMR(400MHz, CDCl3)δ2.60(2H,d),6.66(1H,dd),6.83-6.86(2H,dd),7.06-7.09(3H,dd),7.52(1H,t),7.92(1H,s),8.22(1H,dd)

[0086] [Preparation Example 6]

[0087] Catalyst I-6 was prepared using essentially the same method as in Preparation Example 1, except that 1H-indole-2-carboxaldehyde was replaced with 5,6-difluoro-1H-indole-2-carboxaldehyde.

[0088]

[0089] H 1 NMR(400MHz, CDCl3)δ2.60(2H,d),6.66(1H,dd),6.83-6.86

[0090] (2H,dd),7.06-7.09(2H,dd),7.50(1H,t),7.52(1H,s),8.22

[0091] (1H,dd)

[0092] [Comparison with the preparation example]

[0093] The catalysts for comparison, a and b, have the following structural formulas:

[0094]

[0095] [Examples and Comparative Examples]

[0096] Ethylene / α-olefin copolymers were prepared using different catalysts from the preparation example and the comparative preparation example, respectively, according to the following process:

[0097] Add 500 mL of Isoper E and 300 mL of 1-octene solution to a 2 L stainless steel reactor using a metering pump. Add 2.5 mL of modified methylaluminoxane (MMAO-7), introduce ethylene, and maintain the pressure at 3 MPa. Heat to 130 °C, start stirring, and add a toluene solution (3.2 μmol) of catalyst (added to a spare compartment in the reactor, maintaining nitrogen pressure at 3.5 MPa, then added to the reactor). React at 130 °C for 30 min. After the reaction is complete, depressurize the system, purge with nitrogen three times, and discharge the polymer liquid into a beaker containing 500 mL of ethanol. Filter the precipitated polymer, dry it in a vacuum oven for at least 12 hours, and then measure its physical properties.

[0098] Examples 1-6 use catalysts of formula I-1 to I-6 respectively; Comparative Examples 1-4 use catalysts a, b, c, and d respectively.

[0099] The copolymer evaluation method involved in this invention is as follows:

[0100] (1) Weight-average molecular weight (Mw), molecular weight distribution (MWD), and comonomer content (wt%) of copolymers: The relative molecular mass and distribution of the samples were determined by using a GPC-IR high-temperature gel permeation chromatograph equipped with an IR-5 infrared detector and a viscosity detector, and three Mixed-B columns. The test temperature was 160℃, linear polystyrene was used as a standard, 1,2,4-trichlorobenzene was used as a solvent, and the flow rate was 1.0 ml / min.

[0101] (2) MI of polymers 2.16 The melt index of the polymer, in g / 10min, was measured at 190°C and under a load of 2.16 kg, according to ASTM D 1238.

[0102] (3) Melting point (T) m The melting point of a sample was determined using a differential scanning calorimeter (DSC). 5 mg of the sample was weighed and heated from -40°C to 190°C at a rate of 10°C / min under a nitrogen atmosphere, holding for 5 min to eliminate thermal history. The sample was then cooled to 30°C at a rate of 10°C / min and held for 5 min. The temperature was then raised to 190°C at a rate of 10°C / min, and the change in calorific value was recorded. In the obtained DSC curve, the melting point is the point of maximum endothermic peak during the second heating period.

[0103] (4) Zero-shear viscosity (η0), shear viscosities η1 and η2 at different rotation speeds: The polyolefin sample was dried in a vacuum oven to remove solvent and prevent air bubble interference during testing. The test was conducted in viscosity-shear mode using the parallel plate clamp of a rotational rheometer (TA company, ARGESG2). The test temperature was fixed at 85℃ and the amplitude was 1%. The limiting viscosity value when the shear rate approaches 0 is the zero-shear viscosity. At the same time, the viscosities at angular frequencies of 1 rad / s and 100 rad / s can be obtained. The ratio of the two viscosities is n.

[0104] (5) Content and branching factor (g′) of polymer soluble fraction (SF): Samples were analyzed using a fully automated cross-component fractionation chromatograph (CFC) with 1,2,4-trichlorobenzene as the mobile phase, elution temperature ranging from 10 to 150 °C, and heating rate of 5 °C / min. In TGIC-GPC coupled mode, 2 mg of the polymer sample was dissolved in 1,2,4-trichlorobenzene to form a homogeneous solution, which was then pumped into the chromatographic column. The column was eluted with the trichlorobenzene mobile phase at different temperatures ranging from 10 to 150 °C. Based on the different adsorption capacities of the column for polymer components at different temperatures, the polymer components were fractionated, and the contents of the different soluble fractions obtained after fractionation were recorded. The single fractions obtained after TGIC fractionation were then fed into a high-temperature gel permeation chromatographic column.

[0105] The intrinsic viscosity [η] of each fraction (or peak) of the sample was recorded simultaneously using the GPC-Visco mode. sample The test method uses a viscometer with four capillaries arranged in a Wheatstone bridge configuration and two pressure sensors to determine the specific viscosity. One sensor measures the total pressure drop across the detector, while the other sensor, located between the two sides of the bridge, measures the pressure difference. The specific viscosity η of the solution flowing through the viscometer is calculated from their outputs. s The intrinsic viscosity [η] at each point in the chromatogram. sample From equation [η] sample =η s / c calculation, combined with the Mark-Houwink relation, to calculate the linear intrinsic viscosity [η] of polyethylene at the same molecular weight. linear The intrinsic viscosity [η] of the sample obtained in the experiment. sample The calculated linear intrinsic viscosity of polyethylene [η] linear The ratio is the branching factor g′.

[0106] The copolymers obtained in each embodiment and comparative example were evaluated for the properties shown in Table 1, and the results are as follows:

[0107] Table 1

[0108]

[0109]

[0110] As shown in Table 1, the ethylene / α-olefin copolymers prepared according to the present invention satisfy all zero-shear viscosity η0 and ratio n defined in the present invention. Conversely, Comparative Example 1 satisfies the range of zero-shear viscosity η0, but the viscosity ratio n does not conform to the limitations of the present invention. Comparative Example 2, although its viscosity ratio n conforms to the limitations of the present invention, has a zero-shear viscosity η0 higher than the range of the present invention. Comparative Example 3 has a viscosity ratio n conforming to the limitations of the present invention, and its zero-shear viscosity η0 also conforms to the range of the present invention, but the mass percentage of the 40°C rinsing fraction is low, approaching linear viscosity. Comparative Example 4 has a viscosity ratio n conforming to the limitations of the present invention, and its zero-shear viscosity η0 also conforms to the range of the present invention, and the mass percentage of the 40°C rinsing fraction also conforms to the range, but its branching factor g′ is high, directly causing the sample surface to become sticky, which is detrimental to production and transportation.

[0111]

Application Example

[0112] Using the different ethylene / α-olefin copolymers mentioned above as raw materials, photovoltaic encapsulation films were produced according to the following methods:

[0113] Add 9g of 2-ethylhexyl tert-butyl peroxide, 5g of triallyl isocyanurate, 2g of γ-methacryloyloxypropyltrimethoxysilane, 1g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 1g of bis[2,4-di-tert-butylphenyl]pentaerythritol diphosphite and 1g of β-[3,5-di-tert-butyl-4-hydroxyphenyl]propionate n-octadecyl alcohol ester to 1000g of ethylene / α-olefin copolymer. The above raw materials are heated to 50°C and mixed evenly. The extruder parameters are adjusted so that the temperature from the feed port to the die head is 80°C, 85°C, 85°C, 85°C, 85°C, 90°C, 90°C, 90°C, and the screw speed is 100 rpm. A plain-weave melt filter with a disc diameter of 30 mm and an accuracy of 50 μm is used. The traction speed is 0.7 rpm and the winding speed is 1.3 rpm. After extrusion, casting, cooling, slitting, and winding processes, a photovoltaic encapsulation film with a thickness of 0.6 mm is prepared.

[0114] The photovoltaic encapsulation film evaluation method involved in this invention is as follows:

[0115] Transmittance test: The transmittance at 550nm was measured using a Shimadzu UV-3600 spectrophotometer with a wavelength interval of 1nm and a measurement rate of medium.

[0116] Peel strength test: The peel strength between the tensile glass and the adhesive film was measured at a tensile speed of 100 mm / min, in accordance with the test method of GB / T 2790-1995.

[0117] The processing and physical properties of photovoltaic encapsulation films prepared in different embodiments and comparative samples are shown in Table 2:

[0118] Table 2

[0119]

[0120]

[0121] As shown in the table, the ethylene / α-olefin copolymer provided by this invention significantly reduces the outlet pressure of the filter during melt extrusion, which is beneficial for continuous and stable production and greatly reduces production energy consumption. Simultaneously, the resulting photovoltaic encapsulation film also exhibits higher light transmittance and peel strength, making it more suitable for applications in the electronics and photovoltaic fields.

[0122] The above description is only a preferred embodiment of the present invention. It should be noted that those skilled in the art can make several improvements and additions without departing from the method of the present invention, and these improvements and additions should also be considered within the scope of protection of the present invention.

Claims

1. An ethylene / α-olefin copolymer characterized in that, The application comprises the following features: a) melting point T m 50-75 °C; b) at a temperature of T m + 15°C to T m + 30°C, the zero shear viscosity η0is 1 x 10 4 - 8 x 10 4 Pa-s; c) the ratio of the viscosities n at a shear rate of 1 rad / s and 100 rad / s is 8-22 at a temperature of T m +15°C to T m +30°C. d) The mass percentage of the eluted fraction of the cross-fractionation chromatography CFC test at 40℃ is 0.5-1.2wt%, and the branching degree factor g' ranges from 0.90 to 0.

97.

2. The ethylene / alpha-olefin copolymer of claim 1, wherein The weight average molecular weight of the ethylene / α-olefin copolymer is 30000-150000, and the molecular weight distribution is 1.8 to 3.

5.

3. The ethylene / alpha-olefin copolymer of claim 1, wherein The melt index MFR of the ethylene / α-olefin copolymer at 190℃ and under a load of 2.16kg is 1-30g / 10min.

4. The ethylene / alpha-olefin copolymer according to any one of claims 1 to 3, characterized in that, The α-olefin copolymer is selected from one or more of propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-heptene, 1-octene, 1-decene, 1-undecene, 1-dodecene, 1-tetradecene, 1-hexadecene and 1-eicosene.

5. The ethylene / alpha-olefin copolymer according to any one of claims 1 to 4, characterized in that, The α-olefin content in the ethylene / α-olefin copolymer is 20-50wt%.

6. A process for the preparation of an ethylene / alpha-olefin copolymer according to any one of claims 1 to 5, characterized in that, The application comprises the following steps: Ethylene and α-olefin are polymerized in the presence of a transition metal catalyst represented by formula I to produce an ethylene / α-olefin copolymer; wherein R1 and R2 are each independently selected from hydrogen, fluorine; wherein R3is selected from hydrogen, C1-C 20 alkyl, C3-C 20 cycloalkyl, C2-C 20 straight-chain alkyl terminal alkenyl, C1-C 20 alkoxy, C6-C 20 aryl, C7-C 20 arylalkoxy, C7-C 20 arylalkyl; M is selected from Ti, Zr or Hf.

7. The process for preparing an ethylene / alpha-olefin copolymer according to claim 6, characterized in that, A co-catalyst is also added to the polymerization system, and the co-catalyst comprises an organic compound containing a Group ⅢA element.

8. The process for preparing an ethylene / alpha-olefin copolymer according to claim 7, characterized in that, The co-catalyst comprises any one of the compounds represented by formula II, formula III and optionally a compound represented by formula IV: -[Al(R a )-O] n -Ⅱ wherein R a selected from C1-C 10 alkyl, halogen-substituted C1-C 10 alkyl, n > 2; A(R b )3Ⅲ wherein R b selected from C1-C 20 alkyl, halogen-substituted C1-C 20 alkyl, A is aluminum; [D-H] + [ZT4] - Ⅳ wherein [D] + is an organic cation; Z is a Group IIIA element; T is selected from R c substituted or unsubstituted C6-C 20 aryl, R c substituted or unsubstituted C6-C 20 alkyl, R c selected from halogen, C1-C 20 alkyl, C1-C 20 alkoxy, C6-C 20 phenoxy.

9. The process for preparing an ethylene / alpha-olefin copolymer according to claim 8, characterized in that, The amount of the compound represented by formula II and / or formula III used in the polymerization reaction is 50-1000 times relative to the molar amount of the transition metal catalyst; The amount of the compound represented by formula IV used in the polymerization reaction is 0-10 times relative to the molar amount of the transition metal catalyst.

10. Use of the ethylene / α-olefin copolymer according to any one of claims 1-5 or produced by the method according to any one of claims 6-9 in a photovoltaic packaging film.